2022
DOI: 10.7717/peerj.14052
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 overexpression attenuates breast cancer cell growth and migration by regulating the pyruvate kinase M2-mediated Warburg effect via the PI3K/AKT signaling pathway

Abstract: This work explored the mechanism of the effect of breast-cancer susceptibility gene 1 (BRCA1) on the metabolic characteristics of breast cancer cells, including the Warburg effect and its specific signaling. We transfected MCF-7 cells with a BRCA1-encoding LXSN plasmid or PKM2 siRNA and examined cancer cell metabolism using annexin V staining, inhibitory concentration determination, Western blotting, glucose uptake and lactic acid content measurements, and Transwell assays to assess glycolytic activity, cell a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Dysregulation of let-7b has also been observed in BRCA2 germ-line mutation carriers between invasive breast cancer and asymptomatic normal breast tissue [ 44 ]. Furthermore, BRCA1 has been found to repress HK2 expression, reducing glycolysis and attenuating BC cell migration [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of let-7b has also been observed in BRCA2 germ-line mutation carriers between invasive breast cancer and asymptomatic normal breast tissue [ 44 ]. Furthermore, BRCA1 has been found to repress HK2 expression, reducing glycolysis and attenuating BC cell migration [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, a switch from PKM1 to PKM2 has been detected in various cancers, and a reverse isoform shift from PKM2 to PKM1 has been found to inhibit aerobic glycolysis and reduce tumorigenesis in multiple xenograft models [71]. In particular, recent findings point to an Akt-dependent pro-tumor modulation of PKM2 [72][73][74][75][76][77], which has also emerged as an upstream regulator of the PI3K/Akt pathway itself [78][79][80][81]; in particular, it seems to be able to activate mTORC1 by interacting with Akt1 substrate 1 (Akt1S1) [82]. In this context, aberrant PKM2 expression has been widely associated with poor prognosis in patients with solid tumors of the digestive system, such as esophageal, gastric, colorectal and liver carcinoma [83][84][85].…”
Section: The Pi3k/akt Cascade and Glucose Metabolism In Cancermentioning
confidence: 99%
“…Continuous aerobic glycolysis has been demonstrated to trigger oncogene development in the cancer cells. Aerobic glycolysis is known as the Warburg effect and is one of the tumor hallmarks (Liu et al, 2022a). The enhanced Warburg effect is closely linked to EMT and (2021b) reported that zinc finger E-box-binding homeobox 1 (ZEB1), predicting worse overall survival in cancer patients, facilitated tumorigenesis and metastasis of HCC by enhancing the Warburg effect.…”
Section: Hif-1α Facilitates the Progression Of Hcc By Promoting The W...mentioning
confidence: 99%
“…Continuous aerobic glycolysis has been demonstrated to trigger oncogene development in the cancer cells. Aerobic glycolysis is known as the Warburg effect and is one of the tumor hallmarks ( Liu et al, 2022a ). The enhanced Warburg effect is closely linked to EMT and poor patient prognosis in multiple cancer, including HCC.…”
Section: Hif-1α Facilitates the Progression Of Hcc By Promoting The W...mentioning
confidence: 99%